PENGELOLAAN GOOGLE CLASSROOM OLEH SEKOLAH SEBAGAI PLATFORM PEMBELAJARAN DARING DI MTS DARUL HIKMAH PEKANBARU - Elmuti’ah, Rafika; Nurzakiah, Nurzakiah; Zulhelmi, Zulhelmi (STKIP Pesisir Selatan, 2021)
This study aims to determine the management of Google Classroom by schools as an online learning platform at MTs Darul Hikmah Pekanbaru carried out because researchers want to see learning activities carried out online during the Covid-19 pandemic. Schools need a suitable and controlled learning platform for learning activities, in this case MTs Darul Hikmah uses Google Classroom as its learning platform. The purpose of this study was to find out how to manage Google Classroom by schools along with the advantages and disadvantages of managing Google Classroom by schools at MTs Darul Hikmah Pekanbaru. The research was carried out descriptively through observation and interviews on July 13 to August 18 2020. The results of this study obtained that the steps for managing Google Classroom were starting from sending permission to Google, sending teachers and students into Google Classroom, creating topics, and carrying out learning activities. . Although the management of Google Classroom by this school, teachers can only upload materials during class hours and students need time to search for learning materials on certain topics, the management of Google Classroom by schools can make it easier for schools to control teaching and learning activities, teachers also no longer need to send evidence online class attendance and students also only need to enter one class.